Relative status and satisfaction - Stefan Boes; Kevin E. Staub; Rainer Winkelmann (University of Zurich, Socioeconomic Institute, 2008)
This paper investigates the relationship between income satisfaction of adult children and their relative economic status, using data from the German Socio-Economic Panel and income rank as an indicator of status. The results show that children appear to compare their actual economic status with that of their parents, deriving large satisfaction gains from an income rank that is higher than that of their parents. The effect is asymmetric with regard to parents, as these seem not to be ifluenced by their children's income rank.
Keywords: D62; I31; 330; happiness; income norm; subjective well-being; Lohnniveau; Sozialer Status; Jugendliche; Vergleich; Eltern; Zufriedenheit; Lebensqualität; Schätzung; Deutschland